MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - ICA RAMADHANI (Departemen Matematika, 2021)
Understanding mathematical concepts is a basic ability that students must have in learning mathematics. But in reality, students’understanding of mathematical concepts is still low because it is in process learning of students is still less active. One of the methods used to activate student learning is to apply the Student Team Achievement Division (STAD) type of cooperative learning model. This study aims to describe theoretically whether the STAD type cooperative learning model can improve students' understanding of mathematical concepts and how the type cooperative learning model STAD can improve students' understanding of mathematical concepts. This research was conducted using a qualitative approach, descriptive research type, and literature study methods. Data collection techniques were carried out literature study. The type of data in this study is textual from secondary sources. This research was conducted by collecting and analyzing related sources to get ideas about the learning model STAD cooperative type and understanding student’s mathematical concepts. Based on the study conducted, it was found that theoretically the STAD type of cooperative learning model could improve students' understanding of mathematical concepts. STAD type cooperative learning can improve students’ understanding of mathematical concepts through RPP and LKPD which make students active in carry out learning activities related to evidence of conceptual understanding and scientific approaches.Keywords__ Understanding Of Mathematical Consepts, Cooperative Learning, STAD